2014
DOI: 10.1016/j.healun.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic patterns of ventricular remodeling and apoptosis in hearts unloaded by heterotopic transplantation

Abstract: Aims Mechanical unloading of failing hearts can trigger functional recovery, but results in progressive atrophy and possibly detrimental adaptation. In an unbiased approach, we examined dynamic effects of unloading duration on molecular markers indicative of myocardial damage, hypothesizing that potential recovery may be improved by optimized unloading time. Methods Heterotopically transplanted normal rat hearts were harvested at 3, 8, 15, 30 and 60 days. 47 genes were analyzed using TaqMan-based microarray,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…In hypertrophic and failing hearts, unloading reverses pathological enlargement of cardiac myocytes and normalizes myocardial mass, while in heterotopically transplanted normal hearts, we find reduction of cellular diameters as well as a relative decrease of myocytes compared with connective tissue, this being termed atrophy ( 19 , 20 ). While the normalization of hypertrophy in the failing unloaded heart can be explained by the disappearance of increased wall stress, which goes along with the initiation of a similar gene expression program in both hypertrophy and after unloading ( 21 ), the atrophy following unloading of a normal rat heart must be an active adaptation to the loss of volume load, which includes autophagy and apoptosis ( 22 ).…”
Section: Unloading-induced Effects: Good and Badmentioning
confidence: 99%
See 2 more Smart Citations
“…In hypertrophic and failing hearts, unloading reverses pathological enlargement of cardiac myocytes and normalizes myocardial mass, while in heterotopically transplanted normal hearts, we find reduction of cellular diameters as well as a relative decrease of myocytes compared with connective tissue, this being termed atrophy ( 19 , 20 ). While the normalization of hypertrophy in the failing unloaded heart can be explained by the disappearance of increased wall stress, which goes along with the initiation of a similar gene expression program in both hypertrophy and after unloading ( 21 ), the atrophy following unloading of a normal rat heart must be an active adaptation to the loss of volume load, which includes autophagy and apoptosis ( 22 ).…”
Section: Unloading-induced Effects: Good and Badmentioning
confidence: 99%
“…The underlying mechanisms are not clear. It was reported that there is a significant increase in caspase-3 mRNA expression and activity after mechanical unloading in a normal unloaded heart ( 22 , 27 , 28 ). In addition, relatively late expression changes in genes involved in the apoptosis process were found at the protein level.…”
Section: Unloading-induced Effects: Good and Badmentioning
confidence: 99%
See 1 more Smart Citation
“…In AHF, the 20S proteasome abundance and activity are decreased commensurate with accumulation of ubiquitinated proteins, suggesting impairment of proteasome-dependent degradation, and reversal of this has been observed with mechanical unloading [51,52]. Autophagy markers including Beclin-1, Atg5-Atg12 conjugate, and LC3-II, which are increased in hypertrophy, are reduced with mechanical unloading in humans and rodents [52,53]. Collectively, these studies indicate that protein and cellular homeostasis mechanisms may be normalized at the protein level by MCS.…”
Section: Changes In Protein Abundance Modifications and Localizationmentioning
confidence: 96%
“…These models are considered "non-volumeloaded" (NL), and have been utilized in almost 90% of published studies since 2000. 33 Brinks et al 34 identified the kinetics of load-dependent regulation of myocardial composition over time in a pre-clinical model to investigate strategies that potentially enhance myocardial recovery. They demonstrated that the HHT model in rats is relevant for human disease.…”
Section: Figurementioning
confidence: 99%